Development of a Project of a Moulding Machine for Fermented Dairy Product (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article presents the development of an automated apparatus that significantly increases production efficiency compared to manual methods. Moreover, the apparatus ensures a more precise and rounded shape of the product, enhancing its appearance and consumer qualities. The automated study also confirms that the apparatus contributes to maintaining the microbiological safety of the product, which is a critical aspect of the food industry. Overall, the results emphasize the efficiency and advantages of the apparatus for kurt production, paving the way for its broader application in the industry.